L'histoire de Bone - Allison, Dorothy (Collection 10/18, 1999)
En Caroline du Sud, les étés sont étouffants. Les soirées se passent sur la véranda, à boire du thé glacé et à raconter des histoires. Ruth Anne Boatwright, surnommée Bone par sa famille et estampillée " bâtarde " par le comté de Greenville, se souvient. Elle revoit sa grand-mère édentée, impertinente, ses tantes farouches, usées par leurs grossesses, ses oncles violents, ivrognes pris au piège de leur misère. Elle se souvient de l'amour qu'elle portait à sa mère et de la haine grandissante qu'elle éprouvait pour son beau-père. Elle se souvient et elle raconte, avec une brutale sincérité, les aspirations d'une petite fille, la violence insoutenable, l'amour obstiné. Ce premier roman largement autobiographique, écrit pour exorciser cette enfance brûlée, a été finaliste pour le National Book Award en 1992
Keywords: 1900-1999; 1950-1959; amériques; approches et analyses; inceste; inégalités; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences; états-unis

Pretty in punk: girls' gender resistance in a boys' subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; culture populaire; entretien; ethnographie; genre; harcèlement sexuel; montréal; nouvelle-orléans; patriarcat; périodes historiques; régions géographiques; résistance; san francisco; stéréotypes de genre; systèmes d'oppressions; thématiques; violences

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Feminist visions of development: Gender analysis and policy - Jackson, Cecile; Pearson, Ruth (Routledge, 1998)
Dans le sillage de la 4e Conférence mondiale sur les femmes, cet ouvrage réunit des spécialistes de premier plan du genre et du développement qui interrogent les vingt dernières années de travaux dans ce domaine. Visions féministes du développement jette un nouvel éclairage sur des questions clés telles que : * le genre et l'environnement * l'éducation * la population * les droits reproductifs * l'industrialisation * la politique macroéconomique * la pauvreté. Inspiré par les travaux théoriques féministes récents, il réexamine les analyses structurelles antérieures et ouvre la voie à de nouvelles recherches dans ce domaine.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; droits des femmes*; projet charge mentale; périodes historiques; santé; thématiques; travail; violences

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (De mémoire de femmes, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Kanehsatake 270 ans de résistance - Obomsawin, Alanis; Koenig, Wolf; Dionne, Claude; Teufel, Dagmar; Vallée, Jacques; Office national du film du Canada (Office national du film du Canada, 1993)
"Par une chaude journée de juillet 1990, une confrontation historique a propulsé les problèmes des Autochtones de Kanehsatake et du village d'Oka au Québec au premier plan de la scène internationale et de la conscience des Canadiens. Au cours de cet été épuisant, la productrice et réalisatrice Alanis Obomsawin, elle-même Indienne abénaquise, a passé 78 jours et nuits angoissants derrière les barricades dressées par les Mohawks, à tourner des images du conflit armé les opposant à la Sûreté du Québec et l'Armée canadienne."--Conteneur.
Keywords: 1900-1999; 1990-1999; Kanehsatake; amériques; approches et analyses; canada; cinéma; communication; cours; discipline; féminisme autochtone; justice sociale; militance; oka; premier cycle; premières nations; périodes historiques; québec; régions géographiques; résistance; sex2283; thématiques; violences

Feminist Debates about Women and National Socialism - Grossmann, Atina (Gender & History, 1991)
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; cours; discipline; europe; fascisme; his4830; histoire; histoire des femmes*; histoire et politique; historiographie; holocauste; maternité; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; thématiques; violences; violences contre les femmes*; violences d'état; violences sexuelles

Carol - Highsmith, Patricia (Calmann-Lévy, 1990)
Elles se regardèrent au même instant. Thérèse avait levé les yeux de la boîte qu’elle était en train d’ouvrir et la femme venait de tourner la tête vers elle. Elle était grande et blonde, longue silhouette gracieuse dans un ample manteau de fourrure, qu’elle tenait entrouvert, la main posée sur la hanche. Ses yeux étaient gris, décolorés et pourtant lumineux comme le feu, et ceux de Thérèse, captifs, ne purent s’en détacher. Elle entendit la cliente qui lui faisait face répéter une question et elle resta muette. La femme la regardait, elle aussi, l’air préoccupé comme si une partie de son attention était fixée sur l’achat qu’elle s’apprêtait à faire et, bien qu’il y eût plusieurs vendeuses entre elles deux, Thérèse fut certaine qu’elle allait venir vers elle. Carol est le récit d’une obsession. Refusé à l’origine par son éditeur américain, ce roman a paru une première fois en France sous le titre Les Eaux dérobées signé du pseudonyme de Claire Morgan. Sa réédition permet de redécouvrir l’un des ouvrages les plus marquants du XXe siècle, injustement méconnu. Si le sujet ne fait aujourd’hui plus scandale, Carol conserve son odeur sulfureuse et figure parmi les oeuvres cultes de la littérature lesbienne. Patricia Highsmith y dévoile avec force et sensibilité un amour qui revendique sa liberté dans l’Amérique des années 50.
Keywords: 1900-1999; 1950-1959; amour; amériques; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; roman; régions géographiques; sexualité; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis